PENGARUH PENYULUHAN DENGAN MEDIA DENTAL SPINNING WHEEL GAME TERHADAP PENGETAHUAN TENTANG MAKANAN KARIOGENIK PADA SISWA/I KELAS IV DI SDN 4 GUNTUNG MANGGIS BANJARBARU - Putri, Ayu; Kisworo Utami , Naning; Isnawati, Isnawati; Amperawati, Metty (JURNAL TERAPIS GIGI DAN MULUT, 2025)
The high occurrence of oral health problems is influenced by behaviors that consistently neglect dental and oral health conditions. Particularly, concerning cariogenic foods, children often consume six types of cariogenic foods, namely: candies, chocolate wafers, chocolate bars, chocolate bread, doughnuts, and pudding. Efforts to improve knowledge through education about cariogenic foods can be made. Among the potential strategy that can be used is by using a playful method utilizing the dental spinning wheel game media. This study aims to ascertain the effect of counseling using the dental spinning wheel game media on knowledge about cariogenic foods among fourthgrade students at SDN 4 Guntung Manggis Banjarbaru. The research method used in this study is a quasi-experiment "One Group Pre-test-Post-test", with knowledge measurement before and after using data processing conducted through the Paired Sample Test. The research population comprises all students in classes IV A and B, with a sample size of 41 individuals, sampled using the total sampling technique. The results of this study reveal that the knowledge before counseling with the dental spinning wheel game media was 60.2, and after counseling it increased to 68.9. Based on the statistical test results using the Paired Sample Test. The conclusion of this study is that counseling with the dental spinning wheel game media influences knowledge about cariogenic foods among fourthgrade students at SDN 4 Guntung Manggis Banjarbaru. The presence of the dental spinning wheel game media can be utilized as a learning strategy to enhance knowledge